A new species of Orthetrum Newman, 1833 (Odonata: Libellulidae) from the Andaman Islands, India - Bedjanič, M.; Kalkman, V.j.; Subramanian, K.a. (Zootaxa, 2020)
Orthetrum andamanicum sp. nov. (holotype ♂: India, Andaman and Nicobar Islands, South Andaman island, Chidiyatapu, N 11.51, E 92.71; 08-xii-1998; deposited in RMNH, Leiden; RMNH.INS.1152911), is described as new to science. Based on additional photographic records, notes on mature males’ life colouration, distribution and habitat of this Andaman endemic are provided.